Analisis eco innovation dan eco intellectual capital pada sustainable performance melalui strategic learning pada UMKM F&B di Jakarta - Helen Gunawan; Sawidji Widoatmodjo (Universitas Tarumanagara, 2026)
This study purpose to determine the empirical influence of Eco Innovation and Eco Intellectual Capital on Sustainable Performance with Strategic Learning as mediation in MSMEs in the Food and Beverage (FnB) sector in Jakarta. Sampling used purposive sampling technique. Data collection through questionnaires on Google Form. Analysis of 120 MSMEs FnB in Daan Mogot, West Jakarta. Data analysis techniques used Partial Least Square - Structural Equation Modeling (PLS-SEM) with SmartPLS software ver 4.1.1.4 Analysis of research data testing includes validity and reliability, R2, Q2, f2, Goodness of Fit (GoF)) and hypothesis testing. shows that Eco Innovation has a positive but not significant effect on Sustainable Performance, Eco Intellectual Capital has a positive and significant effect on Sustainable Performance. Strategic Learning has a strong influence on the relationship between Eco Innovation and Eco Intellectual Capital on Sustainable Performance This research shows the alignment with the Knowledge-Based View (KBV) and Dynamic Capability View (DCV) theories which explain through the importance of combining knowledge, abilities, business experience and adjustments to environmental changes. The role of Strategic Learning that strengthens the implementation of Eco Innovation and Eco Intellectual Capital, so that MSMEs are able to see market opportunities, minimize market and environmental risks and increase the development of MSMEs. Penelitian ini bertujuan untuk mengetahui pengaruh empiris Eco Innovation dan Eco Intellectual Capital terhadap Sustainable Performance dengan Strategic Learning sebagai mediasi pada UMKM sektor Food and Beverage (FnB) di Jakarta. Pengambilan sampel menggunakan teknik purposive sampling. Pengumpulan data melalui kuisioner pada Google Form. Analisis terhadap 120 UMKM FnB di Daan Mogot, Jakarta Barat. Teknik analisis data menggunakan Partial Least Square - Structural Equation Modeling (PLS–SEM) dengan software SmartPLS ver 4.1.1.4 Analisis pengujian data penelitian meliputi validitas dan reliabilitas, R2, Q2, f2, Goodness of Fit (GoF)) dan uji hipotesis.menunjukkan Eco Innovation berpengaruh positif dan namun tidak signifikan terhadap Sustainable Performance, Eco Intellectual Capital berpengaruh positif dan signifikan terhadap Sustainable Performance. Strategic Learning memiliki pengaruh kuat dalam hubungan antara Eco Innovation dan Eco Intellectual Capital terhadap Sustainable Performance. Penelitian ini menunjukan keselarasan dengan teori Knowledge- Based View (KBV) dan Dynamic Capability View (DCV) yang memaparkan melalui pentingnya melalukan kombinasi pengetahuan, kemampuan, pengalaman bisnis dan penyesuaian terhadap perubahaan lingkungan. Peran Strategic Learning yang menguatkan implementasi Eco Innovation dan Eco Intellectual Capital, sehingga UMKM mampu melihat peluang pasar, meminimalisirkan risiko pasar, lingkungan dan meningkatkan perkembangan UMKM.